Interfacial Bonding Enhancement between Cryogenic Conditioned Carbon Fiber and Epoxy Resin Characterized by the Single-Fiber Fragmentation Method. Issue 4 (July 2021) - Li, Wuzhou; Zheng, Liangang; Gao, Yang; Xie, Yuzhe; Xu, Fujun
Carbon fiber (CF) is an important structural material due to its favorable mechanical and physical properties. However, poor interfacial bonding with polymer resin severely affects the mechanical performance of carbon fiber reinforced polymer composites (CFRP). In this study, the single-fiber CFRPs were treated using multi-stage cryogenic approaches to optimize the interfacial shear strength (IFSS) between carbon fiber and epoxy resin. The carbon fiber was pretreated by cryogenic treatment with sharp and slow cooling rates, followed by the same treatment of the single-fiber CFRP composed of the pretreated carbon fiber to reach the optimal interfacial modification. The IFSS value was increased by 27.4% when the carbon fiber was pretreated at a slow cooling rate, and its single-fiber CFRP was treated at a sharp cooling rate.